Interactions Between the Kleptoplastidic Dinoflagellate Shimiella gracilenta and Several Common Heterotrophic Protists - Park, Sang Ah; Jeong, Hae Jin; Ok, Jin Hee; Kang, Hee Chang; You, Ji Hyun; Eom, Se Hee; Park, Eun Chong (Frontiers in Marine Science, 2021)
The newly described dinoflagellate, Shimiella gracilenta, is known to survive for approximately one month on the plastids of ingested prey cells during starvation, indicating kleptoplastidy. To understand the population dynamics of this dinoflagellate in marine planktonic food webs, its growth and mortality rate due to predation should be assessed. Thus, we investigated the feeding occurrence of eight common heterotrophic protists on S. gracilenta. We also determined the growth and ingestion rates of Oxyrrhis marina and the naked ciliate, Rimostrombidium sp. on S. gracilenta as a function of the prey concentration. The common heterotrophic dinoflagellates Gyrodinium dominans, O. marina, and Pfiesteria piscicida and a naked ciliate Rimostrombidium sp. were able to feed on S. gracilenta; whereas, the heterotrophic dinoflagellates Aduncodinium glandula, Gyrodinium jinhaense, Oblea rotunda, and Polykrikos kofoidii were not. Shimiella gracilenta supported positive growth of O. marina and Rimostrombidium sp., but did not support that of G. dominans and P. piscicida. With increasing prey concentrations, the growth and ingestion rates of O. marina and Rimostrombidium sp. on S. gracilenta increased and became saturated. The maximum growth rates of Rimostrombidium sp. and O. marina on S. gracilenta were 0.903 d-1 and 0.645 d-1, respectively. Furthermore, the maximum ingestion rates of O. marina and Rimostrombidium sp. on S. gracilenta were 0.11 ng C predator d-1 (1.6 cells predator-1 d-1) and 35.0 ng C predator d-1 (500 cells predator-1 d-1), respectively. The maximum ingestion rate of O. marina on S. gracilenta is lower than that on any other algal prey reported to date, although its maximum growth rate is moderate. In conclusion, S. gracilenta had only a few common heterotrophic protist predators but could support moderate growth rates of the predators. Thus, S. gracilenta may not be a common prey species for diverse heterotrophic protists but may be a suitable prey for a few heterotrophic protists.